2005
DOI: 10.1152/ajpheart.01037.2004
|View full text |Cite
|
Sign up to set email alerts
|

Retinal arteriolar diameter, blood velocity, and blood flow response to an isocapnic hyperoxic provocation

Abstract: Fisher. Retinal arteriolar diameter, blood velocity, and blood flow response to an isocapnic hyperoxic provocation. Am J Physiol Heart Circ Physiol 288: H2912-H2917, 2005. First published February 11, 2005 doi:10.1152/ajpheart.01037.2004.-The aim of this study was to simultaneously quantify the magnitude and response characteristics of retinal arteriolar diameter and blood velocity induced by an isocapnic hyperoxic provocation in a group of clinically normal subjects. The sample comprised 10 subjects (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 47 publications
5
44
0
Order By: Relevance
“…Consistent with previous studies, [36][37][38][39][40][41][42] we observed a pronounced reduction in retinal vessel diameters, retinal blood velocities, and retinal blood flow during 100% oxygen breathing. We also observed an increase in SO 2 in both retinal arteries and retinal veins, with a more pronounced effect in the latter, which is again comparable to previous data.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, [36][37][38][39][40][41][42] we observed a pronounced reduction in retinal vessel diameters, retinal blood velocities, and retinal blood flow during 100% oxygen breathing. We also observed an increase in SO 2 in both retinal arteries and retinal veins, with a more pronounced effect in the latter, which is again comparable to previous data.…”
Section: Discussionsupporting
confidence: 92%
“…Our data show a reduction of 50 to 60% in retinal blood flow, which is closer to the values obtained in humans. [41][42][43][44][45][46] Studying the response of retinal blood flow to hyperoxia is interesting, because it has been shown to be disturbed early in diabetes. 47 However, the mechanisms which lead to this reduced vasoconstrictor response to hyperoxia are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Given that capillary blood velocities are B0.1 cm/s or lower, as found in animal studies (Villringer et al, 1994;Kleinfeld et al, 1998;Hutchinson et al, 2006), the rationale is to use as low a velocity-encoding level as possible without losing too much detection power, especially with the typical ASL perfusionweighted signal change already being very small. At Venc = 3 cm/s, one is likely to be probing arterioles and perhaps small arteries in addition to capillaries as part of the microvascular compartment, because arterioles and small pial arteries of diameter < 200 mm appear to have flow velocities that range from 1 to 6 cm/s (Kobari et al, 1984;Gilmore et al, 2005;Kisilevsky et al, 2008). Decreasing the bipolar crushing gradients, or in other words, using higher levels of velocity encoding, such as 6 cm/s (b = 0.32 seconds/mm 2 ) and 9 cm/s (b = 0.14 seconds/ mm 2 ) would still exclude significant arterial signal, given that the large conductive arteries in the human brain are known to have flow velocities of 30 cm/s and beyond, as measured in the posterior, middle, and anterior cerebral arteries.…”
Section: Introductionmentioning
confidence: 99%